KOMPOSISI COLLEMBOLA DI KAWASAN PENYANGGA PADA PERKEBUNAN KELAPA SAWIT KILIRAN JAO KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Anggraini, Ririn - (STKIP PGRI Sumbar, 2014)
A study on the composition of Collembola in the buffer zone of the oil palm plantations of KiliranJao, Kecamatan Kamang Baru, Kabupaten Sijunjung was conducted from May until August 2014.This study aims to determine the composition of Collembola and physico-chemical factors of soil.Collembolan samples were collected by using pitfall trap at three stations. In this study, threefamilies of Collembola that belong to three genera and 283 individuals were found. Three familiesand 119 individuals of Collembola were found at station I, followed by station II (three families,three genera and 27 individuals), at stasion III with three families, four genera and 137individuals), respectively. Physico-chemical factors which are measured in these three stationswere soil temperature ranges 27.2-28.2oC, followed by air humidity (66 to 73.5%), soil pH (6.8 to6.9), soil moisture content (16 to 25.1%), and soil organic C content (3.2 to 4.2%), respectively.From this study was concluded that Collembola found at three station consist of three families,four genera with highest density was found at station III.